Virulence And Drug Resistance Pattern Of Escherichia Coli Isolates From Various Clinical Sample - Baral, Soma Kanta (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Introduction: E. coli is one of the most common pathogens, and its infection has resulted in a global burden due to its increased medication resistance and virulence factors. The goal of this study was to examine the drug resistance pattern and pathogenicity properties of Escherichia coli isolates. Methods: Over the course of six months (March 2019-August 2019), a laboratory-based cross-sectional study was done among patients visiting Manmohan Memorial Teaching Hospital in Kathmandu, Nepal. Standard microbiological procedures were used to identify bacterial isolates from clinical specimens. The modified Kirby Bauer disk diffusion method was used to determine antibiotic susceptibilities. The combined disk test method was used to confirm the ESBL and MBL. To determine their virulence, serum bactericidal activity and biofilm productions were determined. Results: 59.60 percent (n=81) of the 136 Escherichia coli isolates were multidrug resistant, 25.70 percent (n=35) were ESBL producers, and 11.80 percent (n=16) were MBL producers. Serum resistance was discovered in 22.8 percent (n=31) of the total isolates, while biofilm formation was found in 19.11 percent (n=26). Amoxycillin had the highest level of resistance (87.5%), whereas Chloramphenicol (93.4%) and Imipenem (80.9%) were the most susceptible antibiotics. Polymyxin B and Colistin sulphate were absolutely sensitive. In our investigation, 61.5 percent of biofilm producers were MDR, with non-beta lactamase types being the most common. MBL producers were discovered to be more serum resistant. Amikacin and Imipenem were found to be more sensitive to biofilm makers. Conclusions: The expression of Escherichia coli virulence factors varied depending on the kind of infection. Escherichia coli has a high rate of multidrug resistance. To minimize the emergence and spread of antibiotic resistance in bacteria, proper identification of drug-resistant bacteria, careful use of antibiotics, and effective antibiotic policy are required.